Busy Board: Evidence from CEOs and Director’s Compensation - Robin, Robin (Jurnal Keuangan dan Perbankan, 2021)
This paper examines the busy board and compensation for CEO and independent directors. The independent variable is the busy board. The sample cover 12.332 observations during the period from 1996 to 2015. The analysis is used unbalanced panel data. In this paper, the methods that used to prove the hypothesis are using regression and econometric methodology. The results show that firms with busy boards likely to increase the CEO and independent director’s compensation. The results also support the hypothesis when eliminating the endogeneity problem. Further, the results are also significant positive when changing the measurement of CEO and independent director’s compensation for robustness results. This research suggests that the busy board is weaker the corporate governance.DOI: https://doi.org/10.26905/jkdp.v25i1.5021